Recent Progress of Mussel‐Inspired Underwater Adhesives. Issue 6 (8th May 2017) - Zhang, Ke; Zhang, Feilong; Song, Yongyang; Fan, Jun‐Bing; Wang, Shutao
Abstract: Underwater adhesion is greatly desired in tissue transplantation, medical treatment, ocean transportation, and so on. However, common commercial polymeric adhesives are rather weakened and easily destroyed in water environment. In nature, some marine organisms, such as mussels, barnacles, or tube worms, exhibiting excellent underwater adhesion up to robust bonding on the rock of sea floor, can give exciting solutions to address the problem. Among these marine organisms, mussels exhibit unique underwater adhesion via the foot proteins of byssus. It has been verified that the catechol groups from the side chain of the mussel foot proteins is the main contribution to the unique underwater adhesion. Hence, inspired by the mussels' underwater adhesion, many mussel‐mimetic polymers with catechol as end chains or side chains have been developed in the past decades. Here, we review recent progress of mussel‐inspired underwater adhesives polymers from their catechol‐functional design to their potential applications in intermediates, anti‐biofouling, self‐healing of hydrogels, biological adhesives, and drug delivery. The review may provide basis and help for the development of the commercial underwater adhesives. Abstract : Inspired by the mussels' underwater adhesion, many mussel‐mimetic polymers have been fabricated with catechol groups, the side chain of the mussel foot proteins, as end chains or side chains in the past decade.